2020
DOI: 10.1002/jbio.202000007
|View full text |Cite
|
Sign up to set email alerts
|

Jones matrix‐based speckle‐decorrelation angiography using polarization‐sensitive optical coherence tomography

Abstract: We show that polarization‐sensitive optical coherence tomography angiography (PS‐OCTA) based on full Jones matrix assessment of speckle decorrelation offers improved contrast and depth of vessel imaging over conventional OCTA. We determine how best to combine the individual Jones matrix elements and compare the resulting image quality to that of a conventional OCT scanner by co‐locating and imaging the same skin locations with closely matched scanning setups. Vessel projection images from finger and forearm sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
(108 reference statements)
0
8
0
Order By: Relevance
“…The performance of OCTAVA was further evaluated using several other published OCTA MIP images of skin and retina [ 56 58 ]. The results are presented in Fig 7 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of OCTAVA was further evaluated using several other published OCTA MIP images of skin and retina [ 56 58 ]. The results are presented in Fig 7 .…”
Section: Resultsmentioning
confidence: 99%
“…The image is 6.8 mm × 6.8 mm, and the MIP spans an axial range of 600 μm. Image reprinted with permission from [ 56 ]. Middle row: OCTA MIP image of mouse ear skin acquired with Telesto OCT system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other experimental imaging techniques that have begun to make headway in multimodal research include polarization-sensitive OCT, photothermal OCT, and optical coherence elastography, which, when combined with more standard techniques, have been shown to allow for the differentiation between depolarizing and birefringent tissue (491,492), establishment of molecular contrast (493)(494)(495)(496), and biomechanical assessment of tissue, respectively (497,498).…”
Section: Oct Technologymentioning
confidence: 99%
“…The feasibility of the proposed angiographic method is also demonstrated for human skin imaging with an advanced Jones-matrix swept-source OCT imaging system. It has been concluded that the use of polarization-based angiography has advantages over conventional OCTA by improving vessel contrast and increasing image signal [36], [37].…”
Section: Introductionmentioning
confidence: 99%